2021
DOI: 10.1021/acsami.1c01021
|View full text |Cite
|
Sign up to set email alerts
|

Printable and Semitransparent Nonfullerene Organic Solar Modules over 30 cm2 Introducing an Energy-Level Controllable Hole Transport Layer

Abstract: For the commercialization of organic solar cells (OSCs), the fabrication of large-area modules via a solution process is important. The fabrication of OSCs via a solution process using a nonfullerene acceptor (NFA)-based photoactive layer is limited by the energetic mismatch and carrier recombination, reducing built-in potential and effective carriers. Herein, for the fabrication of high-performance NFA-based large-area OSCs and modules via a solution process, hybrid hole transport layers (h-HTLs) incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…That would be beneficial to obtaining a homogeneous large-area film. [18][19][20][21] The Y6-series NFAs with the conjugated skeleton of the A-DA'D-A type have been comprehensively studied during the past years. [22][23][24][25] Side chain engineering is an effective strategy to tune the aggregation of the active layer.…”
mentioning
confidence: 99%
“…That would be beneficial to obtaining a homogeneous large-area film. [18][19][20][21] The Y6-series NFAs with the conjugated skeleton of the A-DA'D-A type have been comprehensively studied during the past years. [22][23][24][25] Side chain engineering is an effective strategy to tune the aggregation of the active layer.…”
mentioning
confidence: 99%
“…In addition to MoO x , researchers also introduced other additives, such as WO 3 , [60] VO x , [61] WS 2 , [62] Ag nanowires (Ag NWs), [63] α-In 2 Se 3 , [64] g-C 3 N 4 , [65] nafion [66] and nickel formate dihydrate (NFD), [67] etc., to the PEDOT:PSS solution to tune the WF, [60][61][62][63] improve the conductivity [60,[62][63][64][65] and adjust the surface free energy. [66][67] Zhou et al reported the regulation of BHJ molecular orientations through surface free energy control of PEDOT:PSS for high-performance OSCs (Figure 8).…”
Section: Organic Hole Transporting Materialsmentioning
confidence: 99%
“…Fourth, the fabricated device must have excellent mechanical stability [15,16]. Currently, indium-tin oxide (ITO) transparent electrodes are being applied to various optoelectronic devices, such as liquid crystal displays (LCDs), organic light-emitting diodes (OLEDs), organic photovoltaics (OPVs), and perovskite solar cells due to their excellent transmittance and conductivity [17][18][19][20]. However, in order to improve the electro-optical properties of ITO, a thermal treatment process of 300 • C or higher is required, which makes it difficult to apply to organic-based ultra-flexible substrates [21].…”
Section: Introductionmentioning
confidence: 99%